Acute and chronic cholecystitis in children - Arruti, Cesar H.; Torres, David H. (Cirugía del Uruguay, 1975)
Acquired gall bladder diseases are not frequent in children. They must be considered however, in front of pain in the right upper quadrant. In many cases the primary diagnosis was appendicitis, due to the higher incidence of the latter as well as the frequent irradiation of the pai. to the right lower quadrant in cholecystitis in the children.